2017
DOI: 10.1111/jipb.12574
|View full text |Cite
|
Sign up to set email alerts
|

The polyketide synthase OsPKS2 is essential for pollen exine and Ubisch body patterning in rice

Abstract: Lipid and phenolic metabolism are important for pollen exine formation. In Arabidopsis, polyketide synthases (PKSs) are essential for both sporopollenin biosynthesis and exine formation. Here, we characterized the role of a polyketide synthase (OsPKS2) in male reproduction of rice (Oryza sativa). Recombinant OsPKS2 catalyzed the condensation of fatty acyl-CoA with malonylCoA to generate triketide and tetraketide a-pyrones, the main components of pollen exine. Indeed, the ospks2 mutant had defective exine patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 62 publications
4
55
0
Order By: Relevance
“…Loss of function of these genes often leads to defective pollen wall formation, indicating the important role of lipid metabolism on pollen wall formation. Reported genes involved in phenolic metabolism include Oryza sativa Polyketide Synthase1 (OsPKS1; Wang et al, 2013;Zou et al, 2017), OsPKS2 (Wang et al, 2013;Zhu et al, 2017), No Pollen1 (NP1; Chang et al, 2016;Liu et al, 2017), and DPW2 (Xu et al, 2017). Mutants of these genes also display abnormal pollen wall patterning, suggesting that cross linking between aromatic and aliphatic monomers is also important for pollen wall formation.…”
mentioning
confidence: 99%
“…Loss of function of these genes often leads to defective pollen wall formation, indicating the important role of lipid metabolism on pollen wall formation. Reported genes involved in phenolic metabolism include Oryza sativa Polyketide Synthase1 (OsPKS1; Wang et al, 2013;Zou et al, 2017), OsPKS2 (Wang et al, 2013;Zhu et al, 2017), No Pollen1 (NP1; Chang et al, 2016;Liu et al, 2017), and DPW2 (Xu et al, 2017). Mutants of these genes also display abnormal pollen wall patterning, suggesting that cross linking between aromatic and aliphatic monomers is also important for pollen wall formation.…”
mentioning
confidence: 99%
“…Database searches failed to identify any FST1 transporter orthologue in saffron, although this might also be due to low sequence coverage of this clade in the current datasets available for this species. Flavonol and flavone glycosides were also reported from rice anthers (Zhu et al, 2017) and several MFS-type transporters with roughly 40% sequence identity to FST1 can be found in rice and many other monocots. Their identity is higher than the identity of FST1 to the Arabidopsis NPF2.9, NPF2.10, and NPF 2.11 glucosinolate transporters.…”
Section: Functional Aspects Of Fst1 and Its Flavonol Substratesmentioning
confidence: 99%
“…To explore the role of PL1 in anther cuticle, tapetum and pollen development, we analyzed expression profiles of several known genes, which were critical for anther and pollen development, in WT and pl1 spikelets with anthers from stages 4 to 11 by qRT-PCR. We first monitored CYP703A3 [24], OsACOS12 [26,27], OsPKS2 [28,29] and OsTKPR1 [32], which are required for pollen exine formation and lipid metabolism in tapetal cells. Our analysis showed that the expression levels of these genes were decreased in pl1 (Figure 8A-D).…”
Section: The Pl1 Mutation Altered the Expression Of Genes Related To mentioning
confidence: 99%
“…The outer pollen wall, exine, is mainly composed of sporopollenin [5]. In rice, several genes involved in sporopollenin precursors synthesis and shipping have been found, such as CYP703A3 [24], CYP704B2 [25], Acyl-CoA Synthetase 12 (OsACOS12) [26,27], Polyketide synthase 1/2 (OsPKS1/2) [28][29][30][31], Tetraketide α-pyrone reductase 1 (OsTKPR1) [31,32], ATP Binding Cassette G 15 (OsABCG15) [16,33,34], and OsC4/6 [35]. Among them, CYP703A3, CYP704B2, OsACOS12, OsPKS1/2 and OsTKPR1 may form a sporopollenin metabolon similar to their orthologues in Arabidopsis [5,8,15,31,32,36].…”
Section: Introductionmentioning
confidence: 99%